Complexation of 2-acetylpyridine- and 2-benzoylpyridine-derived hydrazones to copper(II) as an effective strategy for antimicrobial activity improvement - Recio Despaigne, Angel A. (2012)
Complexes [Cu(2AcPh)Cl]·2H 2O (1), [Cu(2AcpClPh)Cl] ·2H 2O (2), [Cu(2AcpNO 2Ph)Cl] (3), [Cu(2BzPh)Cl] (4). [Cu(2BzpClPh)Cl] (5) and [Cu(2BzpNO 2Ph)Cl] (6) were obtained with 2-acetylpyridine-phenylhydrazone (H2AcPh), 2-acetylpyridine-para-chloro- phenylhydrazone (H2AcpClPh), 2-acetylpyridine-para-nitro-phenylhydrazone (H2AcpNO 2Ph), 2-benzoylpyridine-phenylhydrazone (H2BzPh), 2-benzoylpyridine-para-chloro-phenylhydrazone (H2BzpClPh) and 2-benzoylpyridine-para-nitro-phenylhydrazone (H2BzpNO 2Ph). The hydrazones showed poor antibacterial effect against Staphylococcus aureus, Enterococcus faecalis and Pseudomonas aeruginosa but demonstrated significant antifungal activity against Candida albicans. Upon coordination to copper(II) the antibacterial and antifungal activities appreciably increased. H2AcpClPh, H2BzpClPh and their copper(II) complexes (2) and (5), respectively, were as active as fluconazole against C. albicans. © 2012 Elsevier Ltd. All rights reserved.